Suicidal Ideation After Mild Traumatic Brain Injury: A Consecutive Canadian Sample. Issue 3 (3rd July 2017) - Bethune, A.; da Costa, L.; van Niftrik, C. H. B.; Feinstein, A.
Abstract : This study aims to elucidate psychosocial and injury features contributing to SI following concussion or mild traumatic brain injury (mTBI) and the time course for its development. Between 1998 and 2012, a sample of 871 patients referred to a follow-up clinic after concussion treatment in an urban tertiary care ED were consecutively offered enrollment at 3 months post injury. Data from psychiatric and social-demographic assessments were consecutively collected at 2 visits (3 and 6 months after injury) respectively. Chi-square and t-tests were performed to identify associations between variables related with SI. Logistic regression analysis was performed to identify factors independently associated. During the enrolment period, 2, 296 patients with mTBI presented to the ED. 871 adults completed psychiatric and social demographic clinic assessments at 3 months, and 500 returned at 6 months. Suicidal ideation was expressed by 6.3% at 3 months and 8.2% at 6 months. Regression models showed SI independently associated with: speaking English as a second language (ESL) and injury mechanism (MVC passenger) at 3 and 6 months; and history of depression and marital status at 3 months only. SI is common 3 months after mTBI, and appears more at 6 month follow up. These findings suggest earlier screening for predisposing factors and closer monitoring of those at risk for suicidality.